2021
DOI: 10.3389/fvets.2021.748869
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis and Subclinical-Like Infection Associated With SARS-CoV-2 in Two Cats Living in the Same Household in France: A Case Report With Literature Review

Abstract: This report provides the first clinical, radiographic, echocardiographic, and biological description of SARS-CoV-2-associated myocarditis with a 6-month follow-up in a 5-year-old obese male domestic shorthair cat (Cat-1) presented for refractory congestive heart failure, with high cardiac troponin-I level (5.24 ng/ml), and a large lingual ulcer. The animal was SARS-CoV-2 positive on serology. The other cat living in the same household (Cat-2) never showed any clinical sign but was also confirmed SARS-CoV-2 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It was reported previously that a SARS-CoV-2-infected cat developed severe respiratory distress and thrombocytopaenia during a household infection, but it was concluded that an unrelated, pre-existing cardiomyopathy caused the observed pathology [ 54 ]. Here, RT-qPCR testing demonstrated that Cat 2A, a previously healthy middle-aged cat, was infected with SARS-CoV-2, which could cause, or exacerbate, cardiac pathology in cats [ 30 , 31 , 32 ]. SARS-CoV-2 related myocarditis and pneumonia was described in a cat with hypertrophic cardiomyopathy (HCM) [ 32 ], and sudden cardiac death in humans who appeared to be recovering from COVID-19 has been reported [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported previously that a SARS-CoV-2-infected cat developed severe respiratory distress and thrombocytopaenia during a household infection, but it was concluded that an unrelated, pre-existing cardiomyopathy caused the observed pathology [ 54 ]. Here, RT-qPCR testing demonstrated that Cat 2A, a previously healthy middle-aged cat, was infected with SARS-CoV-2, which could cause, or exacerbate, cardiac pathology in cats [ 30 , 31 , 32 ]. SARS-CoV-2 related myocarditis and pneumonia was described in a cat with hypertrophic cardiomyopathy (HCM) [ 32 ], and sudden cardiac death in humans who appeared to be recovering from COVID-19 has been reported [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, RT-qPCR testing demonstrated that Cat 2A, a previously healthy middle-aged cat, was infected with SARS-CoV-2, which could cause, or exacerbate, cardiac pathology in cats [ 30 , 31 , 32 ]. SARS-CoV-2 related myocarditis and pneumonia was described in a cat with hypertrophic cardiomyopathy (HCM) [ 32 ], and sudden cardiac death in humans who appeared to be recovering from COVID-19 has been reported [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the majority of reported natural SARS-CoV-2 infections in felids have been either asymptomatic or subclinical [ 23 ], however, severe sequelae including acute respiratory distress [ 24 ] and myocarditis [ 25 , 26 ] have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical outcomes of feline SARS-CoV-2 infection have been documented ( 23 ), from asymptomatic infections ( 24 ) to mild respiratory signs ( 25 ). More severe sequelae include myocarditis ( 26, 27 ), which can be severe and lead to death or necessitate euthanasia. Estimating the frequency of asymptomatic infections by RT-qPCR is technically challenging as there is a narrow window of positivity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%